2018
DOI: 10.1002/slct.201801364
|View full text |Cite|
|
Sign up to set email alerts
|

Regioselective Synthesis, Antibacterial, Molecular Docking and Fingerprint Applications of 1‐Benzhydrylpiperazine Derivatized 1,4‐Disubstituted 1,2,3‐Triazoles

Abstract: A series of ten 1,4‐Disubstituted 1,2,3‐Triazoles having 1‐benzhydrylpiperazine chemical scaffold were synthesized by one pot Cu (I) catalyzed click reaction and evaluated for their antibacterial activity against Escherichia Coli and Staphylococcus aureus by agar well diffusion method. Amongst all, 2‐chloro‐6‐fluorobenzyl substituted 1,2,3‐Triazole 7 e and 2,4‐dichlorobenzyl Triazole 7 f found to be more active compared to the Ciprofloxacin. To rationalize the binding interaction of compounds and the protein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…A set of 1,4-disubstituted 1,2,3-triazoles tethered to a benzhydrylpiperazine fragment were assayed for their antibacterial potentials against S. aureus and E. coli using the agar well diffusion method. 98 The triazole derivatives 63 and 64 (Fig. 7) were found to be more active than ciprofloxacin was (zones of inhibition: 16.33 and 16.45 mm against S. aureus; 15.63 and 16.15 mm against E.coli respectively).…”
Section: Antimicrobial Activitymentioning
confidence: 96%
“…A set of 1,4-disubstituted 1,2,3-triazoles tethered to a benzhydrylpiperazine fragment were assayed for their antibacterial potentials against S. aureus and E. coli using the agar well diffusion method. 98 The triazole derivatives 63 and 64 (Fig. 7) were found to be more active than ciprofloxacin was (zones of inhibition: 16.33 and 16.45 mm against S. aureus; 15.63 and 16.15 mm against E.coli respectively).…”
Section: Antimicrobial Activitymentioning
confidence: 96%
“…Govindaiah and coworkers have synthesized a fluorinated 1,2,3-triazole derivatives bearing benzhydrylpiperazine moiety 121 ( Supplementary Table S1 ) ( Govindaiah et al, 2018 ). Using agar well diffusion method on E. Coli and S. aureus , antibacterial screening was carried out for compound 121 .…”
Section: Introductionmentioning
confidence: 99%
“…By docking study, it was also found that these two compounds make several hydrogen bonds with DNA Gyrase B of bacteria. 28 Functionalized 1,2,3-triazole nucleosides, 4-chlorophenyl derivative 3a, and 3-methylthiophen derivative 3b displayed significant antibacterial activity against many Gram-positive and Gram-negative organisms. The 4-chlorophenyl derivative of functionalized 1,2,3-triazole nucleosides inhibited E. coli ATCC 10536 with a zone of inhibition of 30 mm that was nearer to zone obtained by standard Cefotaxime (34 mm).…”
Section: 23-triazole-14-dihydropyridine-35-dicarbonitrilesmentioning
confidence: 99%